Nuclear microRNAs in normal hemopoiesis and cancer - John E.J. Rasko; Justin J.-L. Wong (Journal of Hematology & Oncology, 2017)
Abstract Since the discovery of microRNAs (miRNAs) in the early 1990s, these small molecules have been increasingly recognized as key players in the regulation of critical biological processes. They have also been implicated in many diverse human diseases. The canonical function of miRNAs is to target the 3′ untranslated region (3′ UTR) of cytoplasmic messenger RNA to post-transcriptionally regulate mRNA and protein levels. It has now been shown that miRNAs can also bind to the promoter regions of genes or primary miRNA transcripts to regulate gene expression. Such observations have indicated the presence of miRNAs in the nucleus and implied additional non-canonical functions. Nevertheless, the role(s) of nuclear miRNAs in normal hemopoiesis and cancer remains elusive despite a burgeoning literature. Herein, we review current knowledge concerning the abundance and/or functions of nuclear miRNAs during blood cell development and cancer biology. We also discuss ongoing challenges in order to provoke further studies into identifying key roles for nuclear miRNAs in the development of other cell lineages and human cancers.